Force-controlled biting alters postural control in bipedal and unipedal stance - Ringhof, Steffen; Stein, T.; Potthast, W.; Schindler, Hans J.; Hellmann, Daniel (Journal of oral rehabilitation, 2015)
Human posture is characterised by inherent body sway which forces the sensory and motor systems to counter the destabilising oscillations. Although the potential of biting to increase postural stability has recently been reported, the mechanisms by which the craniomandibular system (CMS) and the motor systems for human postural control are functionally coupled are not yet fully understood. The purpose of our study was, therefore, to investigate the effect of submaximum biting on postural stability and on the kinematics of the trunk and head. Twelve healthy young adults performed force-controlled biting (FB) and non-biting (NB) during bipedal narrow stance and single-leg stance. Postural stability was quantified on the basis of centre of pressure (COP) displacements, detected by use of a force platform. Trunk and head kinematics were investigated by biomechanical motion analysis, and bite forces were measured using a hydrostatic system. The results revealed that FB significantly improved postural control in terms of reduced COP displacements, providing additional evidence for the functional coupling of the CMS and human posture. Our study also showed, for the first time, that reductions in the sway of the COP were accompanied by reduced trunk and head oscillations, which might be attributable to enhanced trunk stiffness during FB. This physiological response to isometric activation of the masticatory muscles raises questions about the potential of oral motor activity as a strategy to reduce the risk of falls among the elderly or among patients with compromised postural control.
Gesehen am 25.06.2020